(untitled) (Perspectivas de las Ciencias Económicas y Jurídicas, 2023)
This paper develops three theories of emotions, and their criticisms, and then looks at whether it is possible to draw analytical similarities between emotions and implicit bias studies, in terms of the definition of both phenomena and the practical consequences for responsibility for emotional or biased actions.